Symposium 1: Using Philosophy of Information to look at teaching, technology and networked learning - Norberg, Anders (Proceedings of the International Conference on Networked Learning, 2018)
In this conceptual paper, Luciano Floridi's philosophy of Information (PI) is interpreted and used for generating and presenting alternative or deviating, even provoking, understanding and scenarios on Information and Communication Technologies (ICTs), in connection with teaching and networked learning, today and in the future. The relation between teacher and technology and the functions of networked learning are here in focus for the application of Philosophy of information (PI) on issues of teachers, learners and technology. We are as humans, according to Floridi, presently changing our self-understanding, as we also have done at earlier occasions during history, for adapting to scientific and technological developments while still keeping but also changing our agency as humans. Humans are seen as the only known "semantic engines" in the world. The digital technology we presently use, with ICTs who process information and communicates in networks to other ICTs, changes our position and role as humans, as information-processing earlier was purely human activity. Now we have ICTs that are "syntactical engines"; they can process information both fast and precise, although they have "intelligence as a toaster". Humans today are in PI called "inforgs", living in an "infosphere", where information is the most critical asset, and we increasingly experience the world in informational terms. Floridi categorises ICTs as documenting, communicating and information-processing. A longer historical perspective on ICTs in teaching and learning, from Sumer 2000 B.C. and forward leads here to questioning if not the concepts of distance-, e- and online learning are soon old and obsolete, and mainly were continuing something traditional. What is characteristic for digital ICTs is according to Floridi the processing of information, and what we can find when we look for these ICTs in teaching and learning is Learning Analytics, Adaptive Learning, Calibrated Peer Review and similar ICTs for e-teaching. Furthermore, the general concepts of living together with information-processing ICTs are re-ontologisation, enveloping and transdiegetisation. These concepts describe what the ongoing integration of ICTs affects the human, as a teacher or a learner. Networked learning persists and is highly relevant, but includes also networking with applications of artificial intelligence. A critical discussion wraps up the paper.